Comparison of Carotid Plaque Characteristics Between Men and Women Using Magnetic Resonance Vessel Wall Imaging: A Chinese Atherosclerosis Risk Evaluation Study. Issue 2 (27th February 2021) - Zhang, Lichen; Zhu, Lina; Lu, Mingming; Zhao, Xihai; Li, Feiyu; Cai, Jianming; Yuan, Chun; ,
Abstract : Background: Carotid vulnerable plaque is a major cause of stroke and differs between men and women. Few studies have investigated the differences in carotid plaque features between sexes in a Chinese population. Purpose: To compare carotid atherosclerotic plaque features between men and women in a Chinese population using magnetic resonance imaging. Study type: Cross‐sectional. Subjects: A total of 567 patients (mean age: 61.5 ± 10.1 years; 404 men) who had recent stroke or transient ischemia attack and atherosclerotic plaque in at least one carotid artery. Field strength: A 3.0 T. Sequence: T1‐ and T2‐weighted turbo spin echo, three‐dimensional time‐of‐flight (TOF) fast field echo and magnetization‐prepared rapid acquisition gradient echo sequences. Assessment: Plaque characteristics including lumen area (LA), wall area (WA), total vessel area (TVA), mean wall thickness (MWT), and mean normalized wall index (NWI); presence of calcification, lipid‐rich necrotic core (LRNC), intraplaque hemorrhage (IPH), and fibrous cap rupture (FCR); and percent composition area (%area) were evaluated and compared between men and women. Statistical tests: Independent‐sample t test, Mann–Whitney U test, chi‐square test, and multiple linear and logistic regressions. Results: In symptomatic arteries, men had significantly greater LA (46.2 ± 15.6 mm 2 vs. 40.7 ± 12.9 mm 2, P < 0.05), WA (33.9 ± 11.5 mm 2 vs. 26.3 ± 7.5 mm 2, P < 0.05), and TVA (80.1 ± 20.4 mm 2 vs. 67.0 ± 18.0 mm 2, P < 0.05); higher MWT (1.2 ± 0.4 mm vs. 1.0 ± 0.2 mm, P < 0.05); and higher prevalence of LRNC (72.3% vs. 46.0%, P < 0.05) and IPH (18.6% vs. 4.9%, P < 0.05) compared with women. In asymptomatic arteries, men had significantly greater LA (48.3 ± 16.9 mm 2 vs. 42.1 ± 12.6 mm 2, P < 0.05), WA (32.9 ± 11.0 mm 2 vs. 25.8 ± 6.1 mm 2, P < 0.05), and TVA (81.2 ± 22.1 mm 2 vs. 67.9 ± 16.5 mm 2, P < 0.05); higher MWT (1.2 ± 0.3 mm vs. 1.0 ± 0.2 mm, P < 0.05); higher prevalence of LRNC (67.8% vs. 42.9%, P < 0.05), IPH (14.9% vs. 1.2%, P < 0.05), and FCR (6.4% vs. 1.2%, P < 0.05); and higher %LRNC area (24.8 ± 17.2% vs. 17.8 ± 14.1%, P < 0.05) compared with women. Data conclusion: Men have similar plaque burden but more vulnerable atherosclerotic plaques compared with women in both symptomatic and asymptomatic carotid arteries in a Chinese population. Evidence Level: 4 Technical Efficacy: Stage 3